Solvability of an initial-boundary value problem for a nonlinear pseudoparabolic equation with degeneration - Aitzhanov, S.E.; Tileuberdi, Zh.; Sanat, G. (KU Publ., 2022)
This article is devoted to the solvability of degenerate nonlinear equations of pseudoparabolic type. Such problems appear naturally in physical and biological models. The article aims to study the solvability in the classes of regular solutions of (all derivatives generalized in the sense of S.L. Sobolev included in the equation) initial-boundary value problems for differential equations. For the problems under consideration, We have found conditions on parameters ensuring the existence of solutions and we have proved existence and uniqueness theorems. The main method for proving the solvability of boundary value problems is the regularization method.
Азғындалған сызықты емес псевдопараболалық теңдей үшін бастапқыөшеттік есептің шешілімділігі
Разрешимость начально-краевой задачи для нелинейного псевдопараболического уравнения с вырождением
Keywords: pseudo parabolic equations; degenerate equations; boundary value problems; nonlinear equations; solvability; uniqueness